Treatment Strategies for Tandem Occlusions in Acute Ischemic Stroke - Gemmete, Joseph J.; Wilseck, Zachary; Pandey, Aditya S.; Chaudhary, Neeraj (Seminars in Interventional Radiology, 2020)
There is no consensus for the treatment of a tandem occlusion (TO) in a patient presenting with an acute ischemic stroke. In this review article, we will focus on the controversial treatment strategies for TOs. First, we will discuss treatment options including retrograde, antegrade, and delayed approaches. Second, the role of carotid stent placement versus balloon angioplasty for the extracranial occlusion will be presented. Third, anticoagulation and antiplatelet regimens for the treatment TOs published in the literature will be reviewed. Finally, we will discuss whether there is a role for coil occlusion of the cervical carotid artery or whether staged carotid revascularization days after mechanical thrombectomy of the intracranial occlusion maybe appropriate. The optimal treatment strategy of TO has not been established and further larger trials need to be performed to answer the question.
Keywords: stroke; embolization; stent; angioplasty; occlusion; stenosis; interventional radiology